Comparative analysis of Node.js frameworks - Bartłomiej Zima; Marcin Barszcz (Journal of Computer Sciences Institute)
The aim of the article is to compare two popular NodeJs frameworks. The analysis was performed for the ExpressJs and NestJs frameworks. Two proprietary applications supporting CRUD operations, implemented in these technologies, containing the same functionalities were used for the research. The comparison includes application performance, code metrics, documentation quality and completeness, and community support. The analysis showed that ExpressJs is minimalistic and suitable for less complex applications, while NestJs provides a standardized framework that allows the creation and development of large and complex projects.